995 MULTIPLE ORGANISATIONAL FACTORS IMPROVE MULTI-DISCIPLINARY CARE DELIVERY TO PATIENTS WITH HIP FRACTURES: A QUALITATIVE STUDY. (14th June 2022) - Drew, S; Fox, F; Gregson, C L; Patel, R; Judge, A; Johansen, A; Marques, E M R; Barbosa, E C; Griffin, J; Bradshaw, M; Whale, K; Chesser, T; et al.
Abstract: Introduction: Hip fractures are devastating injuries which incur high healthcare costs. Despite national standards and guidelines, there is substantial variation in hospital delivery of hip fracture care and in patient outcomes. This study aimed to understand organisational processes that facilitate successful delivery of hip fracture services. Method: Forty qualitative interviews were conducted with healthcare professionals involved in delivering hip fracture care at four English hospitals. Interview data were supplemented with documentary analysis of 23 anonymised British Orthopaedic Association hospital-initiated peer-review reports of services. Data were analysed thematically, with themes transposed onto key components of the care pathway. Results: We identified multiple aspects of service organisation that facilitated good care delivery. At admission, standardisation of training in nerve block administration impacted care delivery. During hospital stays, service delivery was improved by integrated, shared-care between orthopaedics and orthogeriatrics, and by strategies to improve trauma list efficiency. Adequately staffed orthogeriatric services and the 'right' skills and seniority mix were important to holistic care provision. Placing patients on designated hip fracture wards concentrated staff expertise. Collaborative working was achieved through multi-disciplinary team (MDT) meetings between key staff, protocols and care pathways that defined roles and responsibilities, MDT documentation, 'joined-up' IT systems within hospitals and with primary care, and shared working spaces such as shared offices and onwards. Trauma and hip fracture coordinators organised care processes and provided a valuable central point of contact within teams. Nominated leads, representing diverse specialties, worked together in MDT planning meetings to develop joint protocols, establish audit priorities, and agree shared goals. Routine, comprehensive monitoring and evaluation of service delivery, with findings shared throughout the MDT, was beneficial. Conclusion: Our study has characterised potentially modifiable elements of successful hip fracture service delivery. Findings are intended to help services overcome organisational barriers towards delivery of high-quality hip fracture services.